A Review on Electronic Commerce (International Journal of Innovative Research in Computer Science & Technology, 2022)
The world economy is undergoing a change.  All business is becoming data as a result of internet  technologies. The pace of technology development is so fast  that emergent ecommerce is now influencing every facet of  how business is but will be done, causing major change in  economic environment. Corporations' reach has been  widened thanks to the Internet. Because of the large quantity  of company information made accessible by the worldwide  Web, which means bringing together the information  transferred between firms, between a company and its  consumers, or between various divisions of a business, new  business prospects are increasing tremendously. Any firm  will no longer be able to disregard data virtual value chains  on such an operational and strategic level. This study  examines the extent, unique aspects of e-commerce  technologies, including potentials of e- commerce. It also  creates a basis for recognizing electronic commerce's  prospects or major research concerns. The focus is on  combining technology or business concepts in an  interdisciplinary approach.
Keywords: Business; Consumer; Electronic; E Commerce Technology; Web Technology